Internal medicine residents’ perceptions and experiences in palliative care: a qualitative study in the United Arab Emirates - Harhara, Thana; Abdul Hay, Dana; Almansoori, Dalal S.; Ibrahim, Halah (BMC Palliative Care, 2022)
Palliative medicine is a newly developing field in the United Arab Emirates (UAE). The purpose of this study was to gain a deeper understanding of the experiences of internal medicine residents providing end-of-life care to patients and their families, and how those experiences shape their learning needs.